Performance Analysis of 10 Mbps Wireless Iconnet in Perumahan Bumi Mi’raj - Bima Alnur; Mulyono; Fitri Amillia; Sutoyo Sutoyo (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The Internet has become a basic need for every human being in carrying out his activities. To find out the quality of the internet network, a measurement called the Quality of Service is needed. Quality of service measurement can help in evaluating the performance of internet network providers. Data collection was carried out by monitoring while using YouTube and conducting video meetings using the Zoom application using the Wirleshark software with a viewing time of 30 minutes using the 10 Mbps Iconnet package. The number of users of the Iconnet internet network in this study amounted to 5 users. The data collected in this study were processed using QUALITY OF SERVICE parameters such as throughput, packet loss, delay, and jittler. Then an analysis was carried out by comparing the data obtained with the TIPHON standard. Data collection was carried out at Bumi Mi'Raj Housing, Jalan Bangau Sakti, Pekanbaru City. The results of the 10 Mbps iconnet network research have a very good delay value with an average of 21.75 ms and a very good packet loss with an average of 0.46%. The jitter parameter is in the good category with an average of 24.80 ms and the throughput parameter is in the bad category with an average of 258 kbps. The use of the 10 Mbps iconnet network can be used to play Youtube videos with 360p quality resolution with a total of 5 users. The more users of the 10 Mbps iconnet network, the effect will be a decrease in the quality of the Quality of Service parameter. The use of the iconnet network is better used on the slowest walk than on the slowest time.